Preliminary Study of The Utilization of Belimbing Wuluh (Averrhoa bilimbi L.) Extract as A Coagulant of Rubber (Hevea brasiliensis Muell. Arg.) Latex - Simamora, Michael Kurniawan; Mulyara, Budi; Rangkuti, Ika Ucha Pradifta; Junaidi (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2024)
Coagulants are commonly used in rubber plantations to coagulate latex. This study aims to determine the effect of incubation time and dose of starfruit extract on coagulation speed, total solid content (TSC), and weight loss of the resulting coagulum. The study was carried out at the Sungei Putih Research Unit, Indonesian Rubber Research Institute in September – October 2023. A Completely Randomized Design (CRD) was applied with two treatments, namely, the incubation period for the extract (A) which consisted of three levels (0 days (A1), 2 days (A2), and 4 days (A3)) and the extract dose (B) consisting of three levels (3 ml (B1), 6 ml (B2), and 9 ml per 20 ml latex (B3)). Each treatment combination was repeated three times. The results indicated that the degree of acidity (pH) of starfruit extract without incubation was around 2.8. After incubation for 2 days, the pH decreased to 2.7, and after 4 days to pH 2.5. The fastest coagulation was obtained in treatment A3B3 for 2.03 minutes after mixing, while the longest was in treatment A1B1 for 7.07 minutes. The highest coagulum TSC was obtained in the A3B1 treatment at 50.30%, while the lowest was in the A2B3 treatment at 27.47%. The highest level of weight loss was found in the A2B2 treatment at 36.80%, while the lowest was in the A3B3 treatment at 23.01%. The use of high doses of starfruit extract can coagulate latex in a short time with low weight loss; thus, it can be used as an organic coagulant.